Continuous hemoglobin measurement during frontal advancement operations can improve patient outcomes - SARAÇOĞLU, AYTEN; ABDULLAYEV, RUSLAN; SAÇAK, BÜLENT; AYKAÇ, ZEYNEP ZUHAL; SAKAR, MUSTAFA (My University, 2022)
Massive hemorrhage in pediatric cranioplasty operations may necessitate blood transfusion, which may cause many complications. Radical-7 Pulse CO-Oximeter (Massimo Corporation, Irvine, CA) can provide continuous hemoglobin concentration (SpHb) measurements noninvasively. In this study, we aimed to evaluate the effects of SpHb measurement on perioperative transfusion management and postoperative patient outcomes. For this retrospective case-control study, we collected the data of pediatric patients undergoing fronto-orbital advancement surgery for plagiocephaly and trigonocephaly between 2018 and 2021. Perioperative SpHb monitoring was performed for patients in the SpHb Group. Other patients that were managed conventionally were considered as the control group (C Group). The data on patients\" demographic and clinical characteristics, intraoperative hemodynamic and laboratory variables such as blood gases, intraoperative blood losses, the amount of the transfused blood products, the length of postoperative intensive care unit (ICU) stay, and the duration of hospital stay were collected. The data of 42 patients were collected, and 29 of these patients were males (69%). In 16 of the patients, SpHb monitoring was performed. The demographic, clinical, and perioperative hemodynamic characteristics of the patients were comparable between the groups. Compared to the C Group, the SpHb Group had significantly lower perioperative packed red blood cell (PRBC) transfusion (136.3 +/- 40.1 vs. 181.5 +/- 74.8 mL, P = 0.015), less postoperative drainage (125.3 +/- 47.7 vs. 185.8 +/- 97.6 mL, P = 0.013), and shorter ICU stay (37.1 +/- 12.0 vs. 64.8 +/- 24.9 h, P < 0.001). There was a positive correlation between the amount of PRBC transfusion and the length of ICU stay (r = 0.459, P = 0.003). Patients with perioperative continuous SpHb measurement have lower intraoperative PRBC transfusion, less postoperative bleeding, and shorter ICU stay. When necessary, SpHb, together with clinical judgment and laboratory confirmation, can be used in decision-making for perioperative PRBC transfusion.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Anesteziyoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Anesthesiology; ANESTEZİYOLOJİ; Klinik Tıp; Klinik Tıp (MED); ANESTHESIOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Anesthesiology and Pain Medicine; Hemorrhage; Noninvasive hemoglobin; Pediatric; Transfusion; PULSE CO-OXIMETRY; ACCURACY; Hemorrhage; Noninvasive hemoglobin; Pediatric; Transfusion